PENGAPLIKASIAN MSPAS DI MSPROJECT PADA PROYEK PEMBANGUNAN GEDUNG KULIAH DAN LABORATORIUM POLITEKNIK PARIWISATA LOMBOK: PENGAPLIKASIAN MSPAS DI MSPROJECT PADA PROYEK PEMBANGUNAN GEDUNG KULIAH DAN LABORATORIUM POLITEKNIK PARIWISATA LOMBOK - Mubarak, Rajabi; Hamdani, Hafiz; Nur, M. yusuf (Bangun Rekaprima, 2025)
Project scheduling is a crucial component of construction management, serving as a reference for controlling time, resources, and project progress. Selecting an appropriate scheduling method is essential to ensure that project implementation proceeds effectively and efficiently. This study examines the application of the Model Schedule Project ala Syafriandi (MSPAS) method in a construction project using Microsoft Project software. MSPAS consists of three main components—planning, scheduling, and tracking—which collectively provide comprehensive information regarding project duration, activity dependencies, resource performance, and progress evaluation. The results indicate that the use of MSPAS enhances project efficiency by reducing the project duration from 270 days to 256 days, as well as decreasing indirect project costs by IDR 298,453,596. Furthermore, 287 critical activities were identified, including preparatory work, structural work, architectural work, mechanical, electrical, and plumbing tasks. Therefore, MSPAS can be considered an effective method for optimizing project time and cost in construction management.